Psychosis as an Evolutionary Adaptive Mechanism to Changing Environments - Scheepers, Floortje E.; de Mul, Jos; Boer, Frits; Hoogendijk, Witte J. (Frontiers in Psychiatry, 2018)
Abstract Background: From an evolutionary perspective it is remarkable that psychotic disorders, mostly occurring during fertile age and decreasing fecundity, maintain in the human population. Aim: To argue the hypothesis that psychotic symptoms may not be viewed as an illness but as an adaptation phenomenon, which can become out of control due to different underlying brain vulnerabilities and external stressors, leading to social exclusion. Methods: A literature study and analysis. Results: Until now, biomedical research has not unravelled the definitive aetiology of psychotic disorders. Findings are inconsistent and show non-specific brain anomalies and genetic variation with small effect sizes. However, compelling evidence was found for a relation between psychosis and stressful environmental factors, particularly those influencing social interaction. Psychotic symptoms may be explained as a natural defence mechanism or protective response to stressful environments. This is in line with the fact that psychotic symptoms most often develop during adolescence. In this phase of life, leaving the familiar and safe home environment and building new social networks is one of the main tasks. This could cause symptoms of “hyperconsciousness” and calls on the capacity for social adaptation. Conclusions: Psychotic symptoms may be considered as an evolutionary maintained phenomenon. Research investigating psychotic disorders may benefit from a focus on underlying general brain vulnerabilities or prevention of social exclusion, instead of psychotic symptoms.